Liraglutide Inhibits Osteoclastogenesis and Improves Bone Loss by Downregulating Trem2 in Female Type 1 Diabetic Mice: Findings From Transcriptomics - Yu, Jie; Shi, Yan-Chuan; Ping, Fan; Li, Wei; Zhang, Hua-Bing; He, Shu-Li; Zhao, Yuan; Xu, Ling-Ling; Li, Yu-Xiu (Frontiers in Endocrinology, 2021)
Backgrounds. Mechanisms of bone fragility in type 1 diabetes (T1D) are not fully understood.Whether glucagon-like peptide receptor (GLP-1R) agonists could improve bone quality in T1D context also remains elusive. Aims. We aimed to explore possible mechanisms of bone loss in T1D and clarify whether liraglutide have effects on bone quality of T1D mice using transcriptomics, . Methods. Female streptozotocin-induced diabetic C57BL/6J mice were randomly divided into 4 groups and received the following treatments daily for 8 weeks: saline as controls; insulin; liraglutide; liraglutide combined with insulin. These groups were also compared to non-STZ-treated normal glucose tolerance (NGT) group. Trunk blood and bone tissues were collected for analysis. Three tibia from each of the NGT, saline treated and liraglutide treated group were randomly selected for transcriptomics. Results. Compared with NGT mice,saline treated T1D mice manifested markedly hyperglycemia and weight loss, and micro-CT revealed significantly lower bone mineral density(BMD) and deficient microarchitectures in tibias.8 weeks’ treatment with liraglutide alone or combined with insulin rescued the decreased BMD and partly corrected compromised trabecular microarchitectures. Transcriptomics analysis showed there were 789 differentially expressed genes mainly mapped to osteoclastogenesis and inflammation pathways.RT-qPCR verified gene expression of Trem2, Nfatc1, Trap and Ctsk were significantly increased in tibia of T1D compared to that in NGT group. Liraglutide treatment alone or combined with insulin could effectively suppress osteoclastogenesis by down-regulating gene expression of Trem2, Nfatc1, Ctsk and Trap. Conclusions. Taken together,increased osteoclastogenesis with upregulated expression of Trem2 played a key role in bone loss of T1D mice. Liraglutide provides protective effects on bone loss in T1D mice by suppressing osteoclastogenesis.